Roles of the PTP61F Gene in Regulating Energy Metabolism of Tribolium castaneum (Coleoptera: Tenebrionidae) - Xu, Kang-Kang; Pan, Bi-Ying; Wang, Yuan-Yuan; Ren, Qian-Qian; Li, Can (Frontiers in Physiology, 2020)
Protein tyrosine phosphatase 1B (PTP1B) is a negative regulator in the insulin signaling pathway. It belongs to a class of non-receptor phosphatases of protein tyrosine phosphatase and can catalyze the dephosphorylation of tyrosine to regulate cell differentiation, growth, and metabolism. However, few studies have focused on the role of PTP1B in regulating energy metabolism of insects. In this study, we investigated the expression profiles and the functions of a PTP1B gene (designated TcPTP61F) in the red flour beetle Tribolium castaneum. Quantitative real-time PCR analysed showed that TcPTP61F was highly expressed in the pupal and adult stages. In adult tissues, TcPTP61F was prominently expressed in the tarsus and head. RNA interference-mediated silencing of TcPTP61F reduced the expression of eight genes in trehalose metabolic and glycolytic pathways. TcPTP61F depletion also caused a significant change in the distribution of trehalose, glucose, and glycogen.. Additionally, knockdown of TcPTP61F inhibited the pyruvate kinase (PK) activity and significantly decreased the adenosine triphosphate (ATP) level. The results suggest that TcPTP61F is indispensible for trehalose and energy metabolism of T. castaneum.